sebuah KOMPARASI SUCCESFUL AGING DAN SELF EFFICACY LANSIA YANG TINGGAL BERSAMA KELUARGA DENGAN LANSIA YANG TINGGAL DI PANTI WERDHA - Nanik Dwi Astutik (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2019)
Backgraund: Increasing elderly growth has not been followed by improved quality of life. Successful aging or becoming old successfully is the goal of developing the final stage in the elderly. In addition to these aspects of self efficacy in the elderly is necessary for the elderly to have confidence and confidence in the daily activities and for the achievement of successful aging. Aim : The purpose of this research is to know the comparison of successful aging and self efficacy in elderly who live with family and stay in the home Werdha. Method: This research is quantitative. Comparative quantitative research design involving 60 respondents consisted of 31 elderly living with families and 29 elderly living in the orphanage. Measuring instruments use successful aging and self efficacy assessments. Data analysis using the Mann-Whitney test. Results :The analysis results of succesful aging differences indicate the value of Assymp.sig (2-tailed) amounted to 0.025 < 0.05, meaning there is a difference between succesful aging in elderly living with families with elderly living in the orphanage and the results of the self efficacy differences indicate the value of Assymp. sig (2-tailed) amounting to 0.021 < 0.05, meaning there is a difference between self efficacy in elderly living with families with elderly living in the orphanage. Conclusion : So it can be concluded that there is a difference of successful aging and self efficacy in the elderly who live with the family and stay in the home Werdha. The difference is because the successful elderly tend to have social support especially from both emotional and material families who can help them in the face of any changes they experience. Well, so that every elderly can achieve successful Aging.